Intramolecular Cyclization of Vinyldiazoacetates as a Versatile Route to Substituted Pyrazoles - Drikermann, Denis; Kerndl, Valerie; Görls, Helmar; Vilotijevic, Ivan (Synlett, 2020)
Vinyldiazo compounds undergo a thermal electrocyclization to form pyrazoles in yields of up to 95%. The reactions are operationally simple, use readily available starting materials, require no intervention of a catalyst, and enable the synthesis of mono-, di- and tri-substituted pyrazoles. With the ability to produce highly substituted pyrazoles and the flexibility in installing various types of substituents, this method constitutes a new entry to this valuable heterocyclic scaffold and may be of interest to all branches of the chemical industry.
Keywords: pyrazoles; vinyldiazoacetates; vinyldiazo compounds; cyclization; electrocyclization